Perfusion-Based Antibody Production in the Ambr® 250 Modular - Vivian Ott; Jan Ott; Andry D. Mannone; Regine Eibl (CHIMIA)
The perfusion mode has become increasingly important in biopharmaceutical production in recent years. A bioreactor system used in many laboratories for the development of monoclonal antibodies (mAbs) production processes is the Sartorius’ Ambr. 250 system. Vessels designed for perfusion mode are only available for its high throughput version, while the modular version of the Ambr 250 is not designed for perfusion mode. In this study, perfusion processes for the production of a mAb with Chinese Hamster Ovary (CHO) cells were realized in the Ambr 250 Modular in combination with Repligen’s ATF 1 single-use device for the first time, to the authors’ knowledge. After testing a semi-perfusion setup in well plates and the Ambr 250, an N−1 perfusion process was developed to produce ultra-high cell densities of more than 150 Å~ 106 cells mL−1 for the inoculation of subsequent mAb production processes. In a second step, continuous mAb production was successfully realized over 23 days in a proof-of-concept experiment, achieving a volumetric productivity of 0.65 g L−1 d−1. The results of the N−1 and continuous perfusion processes were comparable to a 3 L HyPerformaTM Glass bioreactor (Thermo Scientific) with an ATF 2 (Repligen).